Uterine Atony: A Literatur Review - Tresna, I Made Gyanendra Nanda; Maharani, Nyoman Ayu Anindya; Aishwarya, Ni Wayan Devian; Farras, Afif; Juwita, Baiq Pelangi; Yahya, Najla Aulia; Kusuma, Rima Cahyati; Zulkarnaen, Decky Aditya (Jurnal Biologi Tropis, 2024)
Uterine Atony is medical condition characterized by the inability of the uterus to contract after labour which can lead to dangerous postpartum bleeding. This condition occurs when the uterine muscles do not function properly to shrink the size of the uterus after childbirth, allowing blood to collect in the uterine cavity. Uterine atony is one of the main causes of postpartum hemorrhage that contributes significantly to the high maternal mortality rate, especially in Indonesia. The purpose of writing this article is to add information related to uterine atony so that early identification and appropriate interventions can be made in the management of uterine atony to reduce maternal mortality in Indonesia. The review method used is a type of literature review that collects and identifies literature related to topics that discuss the definition, epidemiology, risk factors, pathophysiology, clinical manifestations, diagnosis, management and complications of uterine atony.